1978
DOI: 10.1021/jo00408a030
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of o-phthalaldehyde and thiols with primary amines: formation of 1-alkyl(and aryl)thio-2-alkylisoindoles

Abstract: The fluorogenic reaction of o-phthalaldehyde (OPTA) and /3-mercaptoethanol (MERC) with primary amino acids gives a 1-alkylthio-2-alkylisoindole as the product. The structure of this group of previously unknown isoindoles was determined (1) from an in situ analysia of the adducts formed in solution from OPTA, MERC or ethanethiol (ET), and n-propylamine, (2) from the characterization of solid derivatives of these MERC and ET adducts, and (3) from the studies of two isolable isoindoles (an OPTAltert-butylthiol/n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
90
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(95 citation statements)
references
References 8 publications
5
90
0
Order By: Relevance
“…The reaction in borate was complete within one minute at ambient temperature. In the course of reaction, amino acids bearing primary amino groups form highly fluorescent derivatives which were assigned, by analogy with the reaction with mercaptoethanol or glutathione [26,27], to 1-isoindolyl-(1-thioglycosides) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The reaction in borate was complete within one minute at ambient temperature. In the course of reaction, amino acids bearing primary amino groups form highly fluorescent derivatives which were assigned, by analogy with the reaction with mercaptoethanol or glutathione [26,27], to 1-isoindolyl-(1-thioglycosides) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the molar absorption coefficient of the isoindole ring at 337nm (7.66mM-1 cm-I ), 8) it was confirmed that about 1.25mol of OPA were incorporated into I mol of potato phosphorylase monomer. The increase in the UV absorption at 337 nm reached a maximum after 120 min at 30°C (Fig.…”
mentioning
confidence: 88%
“…The decomposition of 1-alkylthio-2-alkylisoindoles formed in buffered aqueous media have been postulated to be due to autoxidation (78,129) and/or nonoxidative nucleophilic or solvolytic reactions (160) among others (4,6,89). In addition, OPA itself is known to undergo a variety of chemical and photochemical reactions (161)(162)(163)(164)(165)(166).…”
Section: Speculation On Mechanism Of the Micellar Effect(s) On Isoindmentioning
confidence: 99%